2017
DOI: 10.1021/acsami.7b11628
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Boron-Based Substituents To Achieve Phosphorescence in Tellurophenes

Abstract: Previous research in our group showed that tellurophenes with pinacolboronate (BPin) units at the 2- and/or 5-positions displayed efficient phosphorescence in the solid state, both in the presence of oxygen and water. In this current study, we show that luminescence from a tellurophene is possible when various aryl-based substituents are present, thus greatly expanding the family of known (and potentially accessible) Te-based phosphors. Moreover, for the green phosphorescent perborylated tellurium heterocycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…More recently, Rivard and co‐workers expanded their scope by introducing fluorinated aromatic compounds, naphthalenes, and fluorene instead of pinacolboranate esters moieties leading to emission in the orange to red spectrum as well . Interestingly, only the tellurophenes containing trifluormethylated benzenes show satisfactory photophysical properties with an overall quantum yield of 9.5 %, a lifetime of 29.3 μs, and an emission at 595 nm, whereas the emission of the bare naphthalene‐ and fluorine‐substituted tellurophenes was significantly red‐shifted, but the QY turned out to be too low to be detected.…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
“…More recently, Rivard and co‐workers expanded their scope by introducing fluorinated aromatic compounds, naphthalenes, and fluorene instead of pinacolboranate esters moieties leading to emission in the orange to red spectrum as well . Interestingly, only the tellurophenes containing trifluormethylated benzenes show satisfactory photophysical properties with an overall quantum yield of 9.5 %, a lifetime of 29.3 μs, and an emission at 595 nm, whereas the emission of the bare naphthalene‐ and fluorine‐substituted tellurophenes was significantly red‐shifted, but the QY turned out to be too low to be detected.…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
“…In recent years, luminescent organoboron compounds have become the focus of investigations because of their promising luminescent properties [ 2 , 18 , 19 , 20 , 21 , 22 ]. In 2017, Yu et al [ 23 ] synthesized the (E)-3-(((4-nitrophenyl)imino)methyl)-2H-thiochroman-4-olate-BF2 compound (S-BF2; see Figure 1 b) based on the parent molecule (E)-2-(((4-nitrophenyl)imino)-methyl)-naphthalen-1-olate-BF2 (C-BF2; Figure 1 a), and explored the photoluminescence (PL) mechanism experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Rivard and co‐workers were the first group to describe the use of tellurium for purely organic phosphors . To this end, a series of tellurophenes were synthesized showing striking phosphorescence emission with lifetimes in the microsecond range . This first example of the higher chalcogens as efficient AI emitters showed that the influence on the emission of these elements is poorly understood and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%